The evolution of growth faltering in 37 developing countries: A spline-regression approach (OR10-08-19) - Headey, Derek D.; Black, Robert E; Hoddinott, John F.; Menon, Purnima; Victora, Cesar G. (Oxford University Press, 2019)
Childhood height-for-age z-scores (HAZ) have been improving in many countries over the last few decades. Most HAZ faltering in malnourished populations takes place during the first 1000 days of life, in the prenatal period and the first two years after birth, but little is known about how growth faltering evolves over time in countries witnessing significant HAZ improvement. We aimed to quantify the evolution of population-level patterns of growth faltering using a novel analytic approach.